PENEGAKAN HUKUM TINDAK PIDANA DESERSI YANGDILAKUKAN OLEH ANGGOTA TENTARA NASIONAL INDONESIA DI WILAYAH HUKUM PENGADILAN MILITER II-11 YOGYAKARTA - I Made Windra Wicaksana, - (2019)
Crimes committed by the Indonesian National Army Forces (TNI) are very rarely known by the public, so this study aims was conducted to determine the settlement process of criminal acts of desertion committed by members of the Indonesian National Armed Forces (TNI) and examine what are the obstacles in their implementation, then try to find solutions to these obstacles. This research was carried out by the method of normative empirical legal research. In this study also used a qualitative approach with primary legal material interviewing and secondary legal material in the form of legislation, books, and other official documents, as well as tertiary legal material in the form of a large Indonesian dictionary, encyclopedia and others. The conclusions in this study, law enforcement in the process and mechanism of settlement of crimes in Military Court II-11 Yogyakarta against deserters can be described globally that in accordance with Law No. 31 of 1997 concerning Military Courts can be upheld and known in law enforcement in the process and the mechanism for the settlement of criminal acts in military courts which are generally used as guidelines for resolving desertion cases committed by members of the military starting from the stage of investigation, continuing prosecution, then trial and finally the execution stage. While the obstacles or constraints of Military Court II11 Yogyakarta in revealing legal facts to decide in absentia are influenced by personal factors, factors in regulations, procedural factors of investigation, examination, and execution in court